Post-Variscan cooling history of the central Western Sudetes (NE Bohemian Massif, Poland) constrained by apatite fission-track and zircon (U-Th)/He thermochronology - Sobczyk, A.; Danisik, Martin; Aleksandrowski, P.; Anczkiewicz, A. (Elsevier BV, 2015)
Apatite fission track (AFT) and zircon (U-Th)/He (ZHe) dating techniques were combined to reveal post-orogenic history of the Rudawy Janowickie Mts. in the West Sudetes (Bohemian Massif). Permian to Jurassic ZHe ages of 271.2 ± 24.8-171.3 ± 11.5. Ma obtained for crystalline basement rocks indicate post-orogenic cooling and progressive unroofing of the NE Bohemian Massif. On the other hand, Cretaceous ZHe ages of 130.5 ± 8.8-99.7 ± 6.7. Ma prove that the Rudawy Janowickie Mts. region remained under ~ 190. °C during the mid-Cretaceous, suggesting a deep burial. ZHe ages from the Cretaceous sediments located to the east of the Rudawy Janowickie Mts. range between 298.8 ± 16.8 and 181.8 ± 11.9. Ma, documenting that the burial did not exceed 6. km in the axial part of the Intra-Sudetic Through. AFT ages range from 105.9 ± 6.1 to 51.1 ± 4.3. Ma. The Eocene AFT ages revealed by the granite basement and the Cretaceous AFT age revealed by the metamorphic cover suggest the existence of at least two different thermo-tectonic blocks experiencing different post-Variscan cooling and exhumation. AFT results strongly support 3.3-3.5. km exhumation for the Rudawy Janowickie Mts. since the Cenomanian, which in combination with ZHe results, clearly contradicts some of the previously proposed evolutionary scenarios for the Sudetes.